Judicial Consideration of State Financial Loss Calculations by The Audit Board of the Republic of Indonesia and Regional Inspectorates - Matris Ijham; Fenty U. Puluhulawa; Suwitno Y. Imran (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2026)
This study examines judicial considerations in the use of state financial loss calculations prepared by the Audit Board of Indonesia (BPK) and Regional Inspectorates in corruption cases. The research focuses on the legal standing, evidentiary value, and institutional characteristics of calculations produced by both bodies, particularly regarding whether they possess equivalent authority and are derived from comparable evidentiary standards in assisting judges to construct legal reasoning. Employing normative legal research through statutory and conceptual approaches, this study analyzes the position of state financial loss assessments within Indonesia’s criminal justice system. The findings demonstrate that both BPK and Regional Inspectorates possess legally recognized authority to calculate state financial losses within the scope of their respective institutional mandates. However, the determination of evidentiary weight remains subject to judicial assessment in accordance with the principles of proof in criminal proceedings. Consequently, judges retain discretionary authority in evaluating whether such calculations sufficiently establish elements of corruption offenses. In practice, judicial consideration is not limited to financial loss assessments alone, but also incorporates witness testimony, expert opinions, documentary evidence, and the substantive criminal law framework under Law Number 1 of 2023 concerning the Criminal Code. This study contributes to the discourse on evidentiary harmonization and institutional authority in Indonesia’s anti-corruption adjudication system.